Kartoffelproduktion in Benin – Ein Beitrag zur Verringerung von Hunger und Armut in Westafrika - Lindner, Kerstin; CHOUGOUROU, CHÈPO DANIEL; AHOTON, ESSÈHOU LÉONARD; Richert-Pöggeler, Katja R. (My University, 2012)
Potatoes produce more calories per area than any other agricultural crop. The tubers are rich in substances valuable for human nutrition. Furthermore, farmers can sell potatoes on the market thus providing a stable income for their family. Benin is one of the poorest countries in the world. One option to minimize hunger and poverty is to increase potato production. Potatoes are grown in the regions of Alibori and Atakora in the north of Benin covering a total area of 15 to 20 ha.
Keywords: Westafrika; Benin; Kartoffelproduktion; Potato virus Y (PVY); Potato leaf roll virus (PLRV); Quarantäneschaderreger; Ralstonia solanacearum